2017
DOI: 10.1097/pr9.0000000000000586
|View full text |Cite
|
Sign up to set email alerts
|

Nocebo effects in clinical studies: hints for pain therapy

Abstract: IntroductionNocebo-induced algesic responses occurring within clinical contexts present a challenge for health care practitioners working in the field of pain medicine.ObjectivesFollowing the recent research on algesic nocebo effects, the scope of this review is to develop ethically acceptable strategies to help avoid, or at least reduce, nocebo responses within clinical settings.MethodsWe reviewed relevant clinical studies that depict how patient-practitioner interactions may contribute to the reduction of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 52 publications
0
56
0
10
Order By: Relevance
“…The greater one’s expectations for pain to improve (or worsen), the greater pain modulation occurs in the expected direction (Corsi & Colloca, 2017). Shaping placebo to enhance descending modulation and facilitate ongoing engagement with adaptive skills may optimize its clinical manifestation (Klinger, Blasini, Schmitz, & Colloca, 2017). A recent meta-analysis of 27 studies showed that how interventions are presented to patients impacts their pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater one’s expectations for pain to improve (or worsen), the greater pain modulation occurs in the expected direction (Corsi & Colloca, 2017). Shaping placebo to enhance descending modulation and facilitate ongoing engagement with adaptive skills may optimize its clinical manifestation (Klinger, Blasini, Schmitz, & Colloca, 2017). A recent meta-analysis of 27 studies showed that how interventions are presented to patients impacts their pain.…”
Section: Introductionmentioning
confidence: 99%
“…Klinger and colleagues discussed several approaches to optimize placebo response for prescribed analgesic medications (Klinger et al, 2017, 2014). Two examples of strategies designed to enhance positive patient expectations include emphasizing the drug’s positive value while minimizing side effects, as well as carefully explaining the drug’s mechanisms of actions to the patient (Klinger et al, 2017, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One set of patients was not told about the analgesic properties of the medication, a second was told they were receiving powerful pain medication or placebo, and a third was informed that they were receiving a powerful analgesic. This study showed a significant decrease in pain medication use in the third group when compared to the other two groups, and this result suggested that verbal communication influences explicit expectations, and thus placebo and nocebo effects (Blasini et al 2017; Colloca and Finniss 2012; Colloca and Miller 2011c; Klinger et al 2017a; Miller and Colloca 2010; Pollo et al 2001; Schwarz, Pfister, and Büchel 2016, 2018). Expectancies can also be modulated by a person’s emotional appraisal of the situation (in other words, by fear, anxiety, or the prospect of reward).…”
Section: The Expectancy Theorymentioning
confidence: 59%
“…The negative counterpart of the placebo effect is named “nocebo” effect (Colloca, 2017a, 2017b; Klinger, Blasini, Schmitz, & Colloca, 2017), and despite its relevance for modulation of mechanisms and clinical implications, the nocebo phenomenon has received less attention over the past decades than the placebo effect. However, laboratory and translational research is unraveling some of the behavioral and biological mechanisms as well as the clinical implications.…”
mentioning
confidence: 99%